Parents Determination Factors Influencing Incomplete Basic Immunization For Infants In Sorong City, West Papua Province - Alva Cherry Mustamu; Serly A. Markus (Pusat Unggulan Iptek (PUI) Poltekkes Kemenkes Yogyakarta, 2020)
The implementation of complete Indonesian basic immunization has decreased in the period of 2012 - 2015. West Papua is one of the provinces with the lowest immunization coverage, which is 57.1% and the city of Sorong is only 21.9%. This research is to investigate the determinant factors of parents' incomplete basic immunization of infants months in Sorong city, West Papua Province. This study was cross-sectional in design. The subjects consisted of purposive sampling of 134 parents of children aged 1-5 years old, have incomplete basic immunization from immunization records and who visit 10 health centers in Sorong City. Data were collected from parents using questionnaires and immunization records. This study used logistic regression to analyze multivariate data Simultaneously, the mother’s age, education level, occupational status, number of children, the experience of having children, distance to the place of immunization, knowledge, family support, immunization officers and attitudes did not affect the incompleteness basic immunization (f count 1.768). Only the number of children (t = 0.017) and immunization staff support (t = 0.044) which affected the incomplete immunization. sequentially, number of children ( = 0.003), immunization support staff ( = 0.004), distance to immunization site ( = 0.035) and attitudes ( = 0.027) which most contribute to incomplete immunization. The number of children, immunization officers support, distance to immunization site and attitudes which contribute to incomplete immunization.